Altered purinergic receptor‐Ca2+ signaling associated with hypoxia‐induced epithelial‐mesenchymal transition in breast cancer cells. Issue 1 (25th September 2015) - Azimi, Iman; Beilby, Hannah; Davis, Felicity M.; Marcial, Daneth L.; Kenny, Paraic A.; Thompson, Erik W.; Roberts-Thomson, Sarah J.; Monteith, Gregory R.
Abstract : Hypoxia is a feature of the microenvironment of many cancers and can trigger epithelial‐mesenchymal transition (EMT), a process by which cells acquire a more invasive phenotype with enriched survival. A remodeling of adenosine 5′‐triphosphate (ATP)‐induced Ca 2+ signaling via purinergic receptors is associated with epidermal growth factor (EGF)‐induced EMT in MDA‐MB‐468 breast cancer cells. Here, we assessed ATP‐mediated Ca 2+ signaling in a model of hypoxia‐induced EMT in MDA‐MB‐468 cells. Like EGF, hypoxia treatment (1% O2) was also associated with a significant reduction in the sensitivity of MDA‐MB‐468 cells to ATP (EC50 of 0.5 μM for normoxic cells versus EC50 of 5.8 μM for hypoxic cells). Assessment of mRNA levels of a panel of P2X and P2Y purinergic receptors following hypoxia revealed a change in levels of a suite of purinergic receptors. P2X4, P2X5, P2X7, P2Y1 and P2Y11 mRNAs decreased with hypoxia, whereas P2Y6 mRNA increased. Up‐regulation of P2Y6 was a common feature of both growth factor‐ and hypoxia‐induced models of EMT. P2Y6 levels were also significantly increased in basal‐like breast tumors compared to other subtypes and breast cancer patients with higher P2Y6 levels showed reduced overall survival rates. P2Y6 siRNA‐mediated silencing and the P2Y6 pharmacological inhibitor MRS2578 reduced hypoxia‐induced vimentin protein expression in MDA‐MB‐468 cells. P2Y6 inhibition also reduced the migration of mesenchymal‐like MDA‐MB‐231 breast cancer cells. The up‐regulation of P2Y6 appears to be a common feature of the mesenchymal phenotype of breast cancer cells and inhibition of this receptor may represent a novel therapeutic target in breast cancer metastasis. Highlights: EMT in MDA‐MB‐468 cells is associated with a significant reduction in the sensitivity to ATP‐mediated increases in intracellular free Ca 2+ . P2Y6 purinergic receptor mRNA expression is elevated in both EGF and hypoxia models of EMT. Gene silencing and pharmacological inhibition of P2Y6 attenuate hypoxia‐induced vimentin protein expression. P2Y6 pharmacological inhibition reduces cell migration in the mesenchymal‐like MDA‐MB‐231 breast cancer cell line. P2Y6 is enriched in basal‐like breast cancers and breast cancers with lower overall survival.